The Magnaporthe oryzae effector AVR1–CO39 is translocated into rice cells independently of a fungal‐derived machinery. (4th March 2013) - Ribot, Cécile; Césari, Stella; Abidi, Imène; Chalvon, Véronique; Bournaud, Caroline; Vallet, Julie; Lebrun, Marc‐Henri; Morel, Jean‐Benoit; Kroj, Thomas
Summary Effector proteins are key elements in plant–fungal interactions. The rice blast fungus Magnaporthe oryzae secretes numerous effectors that are suspected to be translocated inside plant cells. However, their cellular targets and the mechanisms of translocation are still unknown. Here, we have identified the open reading frame (ORF3) corresponding to the M. oryzae avirulence gene AVR1–CO39 that interacts with the rice resistance gene Pi–CO39 and encodes a small secreted protein without homology to other proteins. We demonstrate that AVR1–CO39 is specifically expressed and secreted at the plant–fungal interface during the biotrophic phase of infection. Live‐cell imaging with M. oryzae transformants expressing a translational fusion between AVR1–CO39 and the monomeric red fluorescent protein (mRFP) indicated that AVR1–CO39 is translocated into the cytoplasm of infected rice cells. Transient expression of an AVR1–CO39 isoform without a signal peptide in rice protoplasts triggers a Pi–CO39‐specific hypersensitive response, suggesting that recognition of AVR1–CO39 by the Pi–CO39 gene product occurs in the cytoplasm of rice cells. The native AVR1–CO39 protein enters the secretory pathway of rice protoplasts as demonstrated by the ER localization of AVR1–CO39:mRFP:HDEL translational fusions, and is correctly processed as shown by Western blotting. However, this secreted AVR1–CO39 isoform triggers a Pi–CO39‐specific hypersensitive response and accumulates inside rice protoplasts as shown by Western blotting and localization of AVR1–CO39:mRFP translational fusions. This indicates that AVR1–CO39 is secreted by rice protoplasts and re‐enters into the cytoplasm by unknown mechanisms, suggesting that translocation of AVR1–CO39 into rice cells occurs independently of fungal factors.